Assessing the Predictive Power of Aptitude Tests on Academic Achievement of Students in Science and Technology Majors - Hapsari, Anindita Dwi; Hidayat, Rahmat (Faculty of Psychology, Universitas Gadjah Mada, 2024)
Aptitude tests are used as part of aptitude assessments. The results of these tests can later serve as the basis for providing study major recommendations for clients who wish to pursue their studies at higher education institutions. Two of the aptitude tests used as part of the aptitude assessment are the Differential Aptitude Test (DAT) and the Flanagan Aptitude Classification Test (FACT) which consisted of comprehension, reasoning, patterns, arithmetic, mechanical reasoning, and speed-accuracy subtests. This research intended to know the predictive power of aptitude tests on academic achievement in higher education institutions, especially in the STEM program. Participants in this study were 179 students (111 female, 68 male) at Universitas Gadjah Mada. All participants had taken an aptitude assessment at a psychological service provider and had undergone their first year of study in the STEM programs. Correlation analysis was carried out with the aptitude test as the predictor and GPA as the criterion. This study found that only the numerical ability subtest had a satisfactory correlation coefficient as a predictor of the academic performance in female STEM students in higher education.